IMPROVING PRODUCTION COST MANAGEMENT IN BATIK MAKING IN KUALA LUMPUR, MALAYSIA - Utomo, Rochmad Bayu; Puspitasari, Kakanita Ari; Hudin, Noraine binti Salleh; Budiantara, Martinus (International Journal of Engagement and Empowerment (IJE2), 2024)
Companies must manage their finances well and in a planned manner. Sound financial management must be balanced with knowledge about finance. Costs are one of the economic elements that must be managed well and correctly. The costs greatly influence the size of a company's profit. One of the cost elements is production costs. This Community Service aims to provide knowledge about calculating production costs in making batik cloth. The training participants were 4 MSME actors in Selangor Malaysia whom Krafrtangan Malaysia appointed. The first stage was a field visit to see the batik cloth production process to see the cost components. The second stage was a presentation regarding the preparation of the HPP report. The third stage was assisting in compiling production costs by calculating the results of field visits. The fourth stage was an evaluation of the community service that had been carried out. The results of the assistance are successful because the 4 MSME actors could compile production costs and see the profit obtained from the sale of the cloth